KEAMANAN JARINGAN WLAN DENGAN METODE FIREWALL FILTERING MENGGUNAKAN MIKROTIK PADA SMP NEGERI 1 DOLOK MERAWAN - Mhd. Ilham; Indra Gunawan; Zulia Almaida Siregar (Lembaga Pengembangan Kinerja Dosen, 2022)
The development of the network has changed, which used to use cables, now many wireless networks are built or commonly called Wireless Local Area Networks (WLAN). The use of the internet is increasingly widespread, starting from government agencies, companies, schools and others. WLAN network currently has a very important role as various information that we are looking for we can easily get on the internet. As well as used to make it easier to do our work such as exchanging and storing data. The internet has benefits if Users use it properly. The internet can also have an impact if it is used improperly, namely students at SMP Negeri 1 Dolok Merawan accessing the website during class hours which can disrupt teaching and learning activities. Then it is necessary to apply the Firewall Filtering method using a proxy router to block and limit websites at certain hours to support better and more comfortable teaching and learning activities.